2021
DOI: 10.1016/j.ejvs.2021.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Limb Graft Occlusion Following Endovascular Aneurysm Repair for Infrarenal Abdominal Aortic Aneurysm with the Zenith Alpha, Excluder, and Endurant Devices: a Multicentre Cohort Study

Abstract: WHAT THIS PAPER ADDSThis study provides real world, midterm follow up data on the performance of three major endograft systems currently in routine use, the Zenith Alpha, Excluder, and Endurant, with regards to limb graft occlusion (LGO) after standard endovascular aneurysm repair. The Zenith Alpha device, external iliac artery (EIA) diameter < 10 mm, and landing in EIA were identified as independent risk factors for LGO.Objective: Limb graft occlusion (LGO) is a serious complication after endovascular aneurys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Bogdanovic et al recently reported a multicenter retrospective cohort study that reconfirmed that anchoring in the external iliac artery and narrowed external iliac diameter were risk factors for IBO after EVAR. Their study also revealed that the Zenith Alpha covered stent system is an independent risk factor for IBO ( 9 ). Poor proximal anchoring zone-inflicted IBO is rarely reported.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Bogdanovic et al recently reported a multicenter retrospective cohort study that reconfirmed that anchoring in the external iliac artery and narrowed external iliac diameter were risk factors for IBO after EVAR. Their study also revealed that the Zenith Alpha covered stent system is an independent risk factor for IBO ( 9 ). Poor proximal anchoring zone-inflicted IBO is rarely reported.…”
Section: Discussionmentioning
confidence: 97%
“…Complex anatomical conditions are usually the main cause of related complications, and are associated with a higher rate of surgical revision (5,6). Iliac branch occlusion (IBO) is a common issue post EVAR, with a reported incidence of approximately 1-8% (5,(7)(8)(9). Either unilateral or bilateral sides can be involved in IBO, and the causes are usually complex, including anatomy, equipment, operator factors, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, incidence of iliac limb occlusion was 14%, which is still comparable to values reported in studies using other devices in normal circumstances ( 21 ). For example, in their Zenith group, Bogdanovic et al reported a 12.4% rate of limb occlusion ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Re-intervention was also performed in one patient who developed limb graft occlusion after undergoing EVAR for an aortoiliac aneurysm. A recent multicenter study reported a limb graft occlusion rate of 5.9 percent in a retrospective cohort of 924 patients undergoing EVAR for abdominal aortic aneurysms (Bogdanovic et al 2021 ; Cochennec et al 2007 ). The rate is likely to be similar in patients undergoing EVAR for IIA aneurysms that coexist with aortoiliac aneurysms.…”
Section: Discussionmentioning
confidence: 99%